PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 6 KADUR KECAMATAN RUPAT UTARA - Siti Rahmah; Zariul Antosa; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study was conducted because of the low learning outcomes of science students of grade V of SDN 6 Kadur, Minimum Criteria of Completion (KKM) set at school is 65. Of the 23 students, the KKM reaches 9 students (46.67%), while students who have not reached the KKM are 14 students (53.33%) with an average grade grade of 57.39. To overcome these problems, the researchers apply cooperative learning model type Make a Match. The purpose of this study is to improve the learning outcomes of science students of grade V SDN 6 Kadur. The result of data analysis found that the average score of base score 57,39 increase in cycle I was 31,43% to 75,43. In cycle II the average score of students also increased by 4.90% to 79.13. At the basic score of students' learning completeness classical science is 39% (not complete). After applied the model of cooperative learning type Make A Match on the first cycle student's classical learning completeness increased to 95% and on the second cycle students' learning completeness classic increased to 100%. Teacher activity at the first meeting of cycle I the percentage was 66.67% with good category. The second meeting increased to 77.78% with good category. At the first meeting of the first cycle of cycle II teacher activity increased to 83.33% with very good category. At the second meeting it increased to 94.44% with very good category. Student activity at first meeting of cycle I the percentage is 55,55% with less category. The second meeting increased to 77.77% with good category. At the first meeting of the second cycle of student activity increased to 83.33% with very good category. At the second meeting it increased to 94.44% with very good category. The increasing of teacher and student activity percentage was also accompanied by the increasing of student's learning outcomes from base score 57,39 to 75,43 in cycle I and 79,13 in cycle II. There has been an increase of 37.88% from the baseline score to cycle II. From the results of the research analysis can be concluded that the application of cooperative learning model type Make a Match can improve the learning outcomes of science students of grade V SDN 6 Kadur.Keywords: Co-operative type Make a Match, science learning outcomes